Analisis kinerja keuangan perusahaan transportasi yang terdaftar di Bursa Efek Indonesia sebelum dan masa pandemi covid 19 - Yulianingtiyas, Ervina Tri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the condition of the financial performance of the transportation sub-sector companies studied before and during the covid 19 pandemic and to analyze and determine differences in the financial performance of the transportation sub-sector companies studied before and during the covid 19 pandemic. The sampling technique used was purposive sampling. The data analysis technique in this study used the Paired Sample T Test and the Wilcoxon Signed Rank Test. The results showed that there was no significant difference to the Solvency Ratio of the Debt to Asset Equity (DER) variable before and during the covid 19 pandemic, there was no significant difference to the Liquidity Ratio of the Current Ratio (CR) variable before and during the covid 19 pandemic and there were differences significant Profitability Ratio Return on Assets (ROA) before and during the covid 19 pandemic.